SIMULATION OF DC TRACTION ENGINE WITH SEQUENTIAL EXCITATION IN A CLOSED SYSTEM FOR PARAMETER REGULATION - Irina G. Romanenko; Maxim I. Danilov (Вестник Северо-Кавказского федерального университета)
The authors reveal a mathematical model for a DC engine with a subordinate control system. The developed software system contains a model for engine start both without parameter regulation and with that. There has been shown the influence of the engine parameters on the quality of the control.